Pengaruh Earning Per Share (EPS) Dan Pertumbuhan Penjualan Terhadap Harga Saham Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Desi Nurul Hikmati Ilahiyah; Nisak Ruwah Ibnatur = Husnul; Ika Sopiah; Nurul Lanoria Putri; Putri Kurnia Sari (AKUNTANSI DEWANTARA, 2021)
On investing in the capital market one thing that must be considered is the stock price. The price of shares offered on a stock exchange is related to the achievements of the company. The share price can be purchased by earnings per share (EPS) and sales growth. The purpose of this study was to study the effect of earnings per share (EPS) and sales growth on the stock prices of pharmaceutical companies listed on the Indonesian stock exchange (IDX). The population in this study were 11 pharmaceutical companies that were accepted on the Stock Exchange and sampled through purposive sampling techniques as many as 9 companies in the 2015-2019 period. This study uses multiple linear regression analysis. EPS partial research results positive and significant EPS on EPS stock prices EPS has tcount (54,435)> ttable (2,02439), on the other hand, partial sales growth, positive and significant effect on stock prices, economic growth, thitung sales value ( -3,525) table (-2.02439). Simultaneous EPS and positive and significant growth in stock prices due to the results obtained Fcount (1560,773)> Ftable (3.25).